Mechanical characterisation of sisal fibres for reinforcing of composite materials with several different surface treatments - C. Romão (2004)
The work described in this paper refers to the mechanical characterisation of sisal natural fibres composite materials. Were made experiences with different surface treatments with the purpose of increasing the adhesion between the fibres and the matrix, and consequently to improve mechanical behaviour of the composite material. A brief description of the production and test setups of the composite materials is made.